2008
DOI: 10.1146/annurev.immunol.26.021607.090421
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily Conserved Amino Acids That Control TCR-MHC Interaction

Abstract: Alpha/beta T cell receptors (TCRs) react with major histocompatibility complex proteins (MHC) plus peptides, a poorly understood phenomenon, probably because thymocytes bearing TCRs that manifest MHC-reactivity too well are lost by negative selection. Only TCRs with attenuated ability to react with MHC appear on mature T cells. Also, the interaction sites between TCRs and MHC may be inherently flexible and hence difficult to spot. Contacts between TCRs and MHC in the solved structures of their complexes were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
345
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(369 citation statements)
references
References 127 publications
(171 reference statements)
21
345
0
3
Order By: Relevance
“…Strikingly, the BV5 genes (highly expressed both in humans and humanized mice) present this Y at position 48. Likewise, it has been reported that the BV6 family contacts the MHC molecules in two instances at position 29 of the CDR1 and at position 54 of the CDR2 [33]. Thus, based on these examples, it is tempting to speculate that contacts between evolutionary-conserved residues in the TCR and MHC molecules during thymic positive selection may explain the high proportion of some hTRBV families in the mature T-cell repertoire.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Strikingly, the BV5 genes (highly expressed both in humans and humanized mice) present this Y at position 48. Likewise, it has been reported that the BV6 family contacts the MHC molecules in two instances at position 29 of the CDR1 and at position 54 of the CDR2 [33]. Thus, based on these examples, it is tempting to speculate that contacts between evolutionary-conserved residues in the TCR and MHC molecules during thymic positive selection may explain the high proportion of some hTRBV families in the mature T-cell repertoire.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, accumulating evidence since the pioneering work of Pannetier et al [31] suggest that there is an inherent bias in the TCR to react with some conserved regions of the MHC molecules, outside of the peptide-binding groove, allowing the 'right' docking of the TCR with MHC molecules for efficient selection [17,32,33]. Recent functional data revealed the important role of Y at position 48 of the hTRBV chain in T-cell positive selection, through contacts with the a domains of both class I and class II MHC molecules [17,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of MHC class-I molecule in response to almost all antigens make the study very interesting. They bind to some of the peptide fragments generated after proteolytic cleavage of antigen [27]. Identification of MHC-binding peptides and T-cell epitopes helps improve our understanding of specificity of immune responses [28].…”
Section: Sonu Mishra and Virendra S Gomasementioning
confidence: 99%
“…Significant changes in TCR CDR3 loops can take place upon binding (57)(58)(59) and CDR3 can occupy different conformations depending upon which ligand is bound (60,61 mechanisms produced occur simul-taneously in the interface, not limited to molecular mimicry and CDR loop shifts (62). Recently, it has been reported that the cross-reactivity correlated with a shrinking, increasingly hydrophobic TCR-ligand interface (63), and a few conserved amino acids in CDR1 and CDR2 were involved in the engagement (63,64).…”
Section: Molecular Basis Of Mhc-i/tcr Interactionmentioning
confidence: 99%